(untitled) (NAWA: Journal of Japanese Studies, 2025)
Vocaloid is not just a music production tool, but a pop culture phenomenon that combines technology, visual art, and fan creativity. The Vocaloid phenomenon began with the launch of Hatsune Miku in 2007 by Crypton Future Media in collaboration with Yamaha. Shortly thereafter, another character known as Mirror Image was released, namely Kagamine Rin and Len. The emergence of these two Vocaloids has revolutionized the Japanese music landscape. Through voice synthesis software, Vocaloid enables individuals to create music without the limitations of human vocalists. The Vocaloid fan community supports collaborative works, from songs to fan art, and hosts live holographic concerts that blur the lines between reality and fiction. This strengthens cross-border community bonds, making Vocaloid one of the most influential digital creative ecosystems of the 21st century. Therefore, the emergence of Miku and Mirror Image significantly influenced the development of popular culture at the time. However, in its development, Mirror Image has been inconsistent in improving its audio and visual quality, making it less popular today. Unlike Mirror Image, Miku has become an enduring symbol of the virtual idol in the “database” industry model, where fans continue to produce and shape their own narratives. This article analyzes the development of Vocaloid as popular culture and compares the character of Hatsune Miku with the character of Mirror Image as part of popular culture.